The impact of COVID‐19 lockdown on children's and adolescents' mental health in Greece - Magklara, Konstantina; Lazaratou, Helen; Barbouni, Anastasia; Poulas, Konstantinos; Farsalinos, Konstantinos (Children & society, 2023)
The aim of the study was to investigate the impact of the COVID‐19 lockdown on children's and adolescents' mental health in Greece during the lockdown of spring 2020. A cross‐sectional survey of 1232 Greek parents was conducted in spring 2020. 35.1% of parents reported that their children's psychological health was significantly affected. Parental unemployment, limited opportunity for tele‐work and deteriorating psychological health, increased family conflicts and children's pre‐existing physical health conditions were all significantly associated with mental health impact. Children and adolescents may experience adverse mental health effects due to the COVID‐19 pandemic.